Quality Assurance Scheme (QAS) in Medical & Dental Colleges in Bangladesh -Teacher's Knowledge (Bangladesh Journal of Medical Biochemistry, 2013)
This cross-sectional study was conducted with the objective to assess the teacher's knowledge about ongoing quality assurance scheme (QAS) at different government and nongovernment medical & dental colleges in Bangladesh. Teachers of different categories were the respondents of this study. Self administered structured questionnaire was used to collect data adopting simple random sampling. The study was conducted in 2008 & 2009. The study revealed that both government and nongovernment medical colleges are conducting the QAS in their respective institutions. The academic coordinator play a vital role to run the QAS and for phase coordination. Students also participate as the representative member of the committee. Existing infrastructure of QAS is performing at its best effort but needs further development for upgradation of the services with an aim to improve the performance of the institutes. Principles of QAS are accountability, selfevaluation and external peer review. Major areas of QAS are organizational & operational frameworks. Organizational framework consists of both academic council and course committee. External examiners are appointed by university. External assessors are appointed by academic council but needs faculty approval. Operational framework consists of course appraisal, faculty development, review scheme, & external review. The study recommends that quality assurance scheme (QAS) should be thoroughly implemented and evaluated by the national quality assurance body. Both the organizational and operational frameworks should run along with faculty development and review scheme. Teachers should be more oriented to update their knowledge for better practices of QAS. DOI: http://dx.doi.org/10.3329/bjmb.v3i1.13800 Bangladesh J Med Biochem 2010; 3(1): 6-10